Nursing care of the community - Famorca, Zenaida U.; Nies, Mary A. ;McEwen, Melanie (Singapore : Elsevier Science, 2013)
A complete textbook for Comunity Health Nursing based on the standards set out in CMO No. 14 of the Commission on higher education and more.
Ch. 1: Fundamental concepts of community health nursing -- Ch. 2: Theoretical foundations of community health nursing practice -- Ch. 3: Primary health care -- Ch. 4: Community organizing: ensuring health in the hands of the people -- Ch. 5: Health promotion, risk reduction, and capacity-building strategies -- Ch. 6: Family health nursing -- Ch. 7: The nursing process in the care of the community -- Ch. 8: Applications of epidemiology in community health -- Ch. 9: The health care delivery system -- Ch. 10: Maternal, newborn, and child health and nutrition -- Ch. 11: Control of noncommunicable diseases -- Ch. 12: Control of communicable diseases -- Ch. 13: Environmental health -- Ch. 14: Disaster management -- Ch. 15: eHealth in the community setting -- Ch. 16: School health -- Ch. 17: Occupational safety and health.
Includes index.
Keywords: COMMUNITY HEALTH NURSING